2015
DOI: 10.1177/1073191115570110
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Traits as Transdiagnostic Predictors of Clinical Problems

Abstract: The National Institute of Mental Health Research Domain Criteria initiative (Insel et al., 2010) calls for a focus on biologically meaningful dimensional constructs in the study of clinical problems. Examples are needed of how Research Domain Criteria constructs can be linked to clinical problems. We examined how two such constructs, threat sensitivity (THT+) and weak inhibitory control (INH−), operationalized using scale measures of fear/fearlessness and inhibition/disinhibition dimensions from established st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
94
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 64 publications
(117 reference statements)
16
94
0
2
Order By: Relevance
“…Weak inhibitory control, characterized in individual-difference terms as trait disinhibition (DIS; L. D. Nelson, Strickland, Krueger, Arbisi, & Patrick, 2016; Patrick et al, 2013), has been identified as a liability factor for externalizing problems of various types, including child and adult antisocial behavior and maladaptive substance use (Krueger, Hicks, Patrick, Carlson, Iacono, & McGue, 2002; Yancey et al, 2013). Patrick and colleagues (2013) constructed a “psychoneurometric” index of DIS, incorporating self-report-scale measures along with brain-response variables, that effectively predicted both clinical-symptom and physiological criterion measures.…”
Section: Methodological Issues In the Use Of Individual Brain Measurementioning
confidence: 99%
See 3 more Smart Citations
“…Weak inhibitory control, characterized in individual-difference terms as trait disinhibition (DIS; L. D. Nelson, Strickland, Krueger, Arbisi, & Patrick, 2016; Patrick et al, 2013), has been identified as a liability factor for externalizing problems of various types, including child and adult antisocial behavior and maladaptive substance use (Krueger, Hicks, Patrick, Carlson, Iacono, & McGue, 2002; Yancey et al, 2013). Patrick and colleagues (2013) constructed a “psychoneurometric” index of DIS, incorporating self-report-scale measures along with brain-response variables, that effectively predicted both clinical-symptom and physiological criterion measures.…”
Section: Methodological Issues In the Use Of Individual Brain Measurementioning
confidence: 99%
“…Conceptualized in individual-difference terms, this construct connects to the general trait dimension shown to underlie psychological-scale measures of fear versus fearlessness in relation to stimuli and situations of various types (Kramer, Patrick, Krueger, & Gasperi, 2012). When operationalized in terms of scores on this fear/fearlessness dimension, variations in threat sensitivity are independent of (i.e., uncorrelated with) variations in inhibitory control, quantified as trait disinhibition (L. D. Nelson et al, 2016; Venables, Sellbom, et al, 2015). High scores on this fear/fearlessness dimension have been found to be related to anxiety disorders of various types, particularly those involving context-bound fear (L. D. Nelson et al, 2016; Yancey et al, 2016); low scores on this dimension, by contrast, are associated with affective-interpersonal (“Factor 1”) symptoms of psychopathy (Patrick & Bernat, 2009; Patrick & Drislane, 2015).…”
Section: Methodological Issues In the Use Of Individual Brain Measurementioning
confidence: 99%
See 2 more Smart Citations
“…En esta misma línea, recientemente se ha demostrado una asociación entre síntomas del trastorno de ansiedad generalizada y una mayor amplitud del P300 en la misma versión de la tarea de flancos empleada en este estudio (Meyer y cols., 2017). Así, esta relación podría ser explicada en términos de que las características de bajo miedo que subyacen al fenotipo de audacia del MTP representan una dimensión que se asocia de forma negativa a distintos indicadores de psicopatología internalizante, incluidos síntomas del trastorno de ansiedad generalizada (Nelson, Strickland, Krueger, Arbisi y Patrick, 2016). En este sentido, es evidente la necesidad de más estudios que exploren las relaciones entre el P300 y el rasgo de ausencia de miedo.…”
Section: Discussionunclassified